Proyecto de inversión para la creación de una empresa que brinde el servicio de planeamiento de eventos en la ciudad de Guayaquil - Plaza Velásquez, Carmen Yomaira (2010)
This project arose from the need to provide people of different social and business event planning service in the city of Guayaquil, the same one responsible for giving the customer convenience and security of their meetings to enjoy without any worried. Service Event Planning is a relatively new field of study, this is the process of design, planning and production of conferences, festivals, ceremonies, festivals, conventions or other meetings, each of which may have different purposes . The main objective is to identify strategies to attract new customers in the local market under a marketing plan aimed at our target market and be the Event Planning company with which the population of the city feel more identified when choosing a option at the same time let us know at the local level.